Does confidence enhance performance? Causal evidence from professional biathlon - Alexander Ahammer; Mario Lackner; Jasmin Voigt (Johannes Kepler University Linz, Christian Doppler Laboratory Aging, Health and the Labor Market, 2017)
We analyze the effect of self-confidence on performance using data from top-level professional biathlon competitions. Biathlon combines two independent tasks: cross-country skiing and rifle shooting. We exploit this dual nature of the sport by using weather conditions affecting performance on the skiing track as exogenous variation in confidence on the shooting range. Using round-level data on 254 competitions between 2009 and 2013, we show that the less confident athletes are, the worse their performance is on the shooting range. In particular, we estimate an increase of 0.525 standard deviations in missed shots for every standard deviation increase in our inverse self-confidence measure. Effects for women are estimated to be generally smaller in magnitude and less robust.
Keywords: J24; Z2; 330; Self-confidence; performance; biathlon; sports economics